Literature Review: Stres Pengasuhan pada Anak dengan Gangguan Spektrum Autisme - Ibrahim, Maulana Hanif; Kalalo, Royke Tony; Irmawati, Mira (Universitas Trunojoyo Madura, 2022)
This literature review aims to examine the results of research on parenting stress in children with autism spectrum disorders that has been carried out for the last ten years, namely in the period 2012 - 2022. The search for research articles was carried out using certain keywords by following the PRISMA guidelines . There were 12 research articles analyzed in this literature review which were obtained through the Google Scholar, SAGE Journals, PubMed, SpringerLink, ScienceDirect, Taylor and Francis Online, and Wiley Online Library databases, which were then analyzed for the purpose, methods, sample, and research findings. The results of this literature review are in line with previous studies regarding the level of parenting stress in children with autism spectrum disorders which showed that parents of children with autism spectrum disorders experienced significantly higher parenting stress than parents of children with other developmental disorders. and children with normal development, and there is a significant difference between the level of stress on mother's care and stress on father's care for children with autism spectrum disorders. There are 3 main factors that relate to and influence the level of parenting stress on parents, namely children, parents, and external factors. Parenting stress has consistently been found to negatively impact parents' quality of life in terms of mental health. Future research can look at socio-cultural factors associated with parenting stress in various cultures so as to add information to the literature on parenting stress and how intervention methods can be given that are culturally appropriate for each parent.